Fiducial markers in adjuvant setting for a patient affected by endometrial cancer: a case report - Titone, Francesca; Restaino, Stefano; Moretti, Eugenia; Vullo, Gianluca; Poli, Alice; Arcieri, Martina; Paglietti, Chiara; Tonetto, Fabrizio; Parisi, Giuseppe; Barbui, Elisa; Trovò, Marco; Scambia, Giovanni; et al. (Frontiers in Oncology, 2023)
Introduction: intermediate-high and high-risk endometrial cancer often require adjuvant treatments such as radiotherapy (RT) or brachitherapy (BT) to reduce the risk of loco-regional relapse. Inter- and intra-fraction variability of internal pelvic anatomy are possibly the largest source of error affecting pelvic RT. The implantation of Fiducial Makers (FMs) in the vaginal cuff of patients receiving RT or BT could help patient daily setup, image guidance and intra-fraction detection of the radiation targets. Clinical case: we have evaluated the case of an 80-year-old woman treated with surgery for endometrioid adenocarcinoma G2 (stage pT1b Nx LVSI+) who underwent adjuvant pelvic IMRT after the implantation of vaginal cuff FMs. CT-simulation, Treatment Planning and IGRT strategy: patient underwent planning CT scan 10 days after FMs implantation. RT consisted of 45Gy in 25 daily fractions to pelvic lymph nodes and surgical bed with simultaneous integrated boost up to 52.5Gy to the vaginal cuff and the upper two-thirds of the vagina. Cone beam Computed Tomography (CBCT) was acquired prior to every RT fraction for IGRT. Bladder and rectum were re-contoured on every CBCTs. Bladder and rectal volumes and median shifts were reported on a prospective database to quantify the impact of the pelvic organ variations. Results: the patient reported no discomfort during the FMs implantation, and no complications were seen. No evidence of FMs migration was reported. Bladder and rectal volumes planned contours were 245 and 55.3cc. Median bladder volumes for approved and “not acceptable” CBCTs were 222cc (range: 130-398) and 131cc (range: 65-326), respectively. Median rectal volumes for approved and “not acceptable” CBCTs were 75cc (range: 58-117) and 90cc (range: 54-189), respectively. The median values of the anterior-posterior, superior-inferior, lateral direction shifts were 3.4, 1.8 and 2.11 mm, respectively. Conclusion: in our clinical case, the implantation of FMs in the vaginal cuff of a patient who underwent pelvic adjuvant RT was well tolerated and reported no complications. The use of IGRT procedures based on FMs surrogating the vaginal vault may reduce inter-observer variability and pave the way for adaptive strategies or stereotactic treatments as external beam pelvic boost in gynecological field.